2021
DOI: 10.1021/acsami.1c00594
|View full text |Cite
|
Sign up to set email alerts
|

Air-Stability Improvement of Solar Selective Absorbers Based on TiW–SiO2 Cermet up to 800 °C

Abstract: A high-temperature air-stable solar selective absorber (SSA) based on TiW–SiO2 cermet is prepared by the co-sputtering method. The obtained SSA shows remarkable stability in spectrum, structure, and chemistry after air-annealing at 700 °C, demonstrating its resistance against air erosion at high temperature. Comparing with W-SiO2-based SSA, the addition of the Ti element is proved to be effective in enhancing the thermal stability of SSA. Nevertheless, as the temperature increases to 750 °C, perfectly round ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Yang et al prepared a high‐temperature stable SSA based on TiW–SiO 2 cermet by cosputtering method. [ 29 ] By adding Ti element, the as‐obtained SSAC shows remarkable stability in spectrum, structure, and chemistry after annealing at 700 °C in air (Figure 2b).…”
Section: Recent Advances In Ssasmentioning
confidence: 99%
“…Yang et al prepared a high‐temperature stable SSA based on TiW–SiO 2 cermet by cosputtering method. [ 29 ] By adding Ti element, the as‐obtained SSAC shows remarkable stability in spectrum, structure, and chemistry after annealing at 700 °C in air (Figure 2b).…”
Section: Recent Advances In Ssasmentioning
confidence: 99%
“…Yang et al utilized the TiW-SiO 2 as absorption layers to prepare SSACs on the quartz substrate. The experimental results showed that incorporating the second phase Ti could effectively improve the stability of the absorber (Yang et al, 2021). In addition, a series of binary alloys (WTa, WNi, TiC, etc) based selective absorbers were proposed and their stable operating temperatures were further enhanced (Cao et al, 2015a;Cao et al, 2015b;Wang et al, 2017;Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Leveraging recent progress in the field of radiative heat transfer and photonic control [26] , [30] , advancements in thermal photonic metamaterials are facilitating the evolution of passive solar heating and radiative cooling technologies. Spectrally selective solar absorbers, such as multi-layered metal-dielectric stacks [15] , [31] , cermets [32] , [33] , and plasmonic nanostructures [34] , [35] , have been validated with spectral manipulation achievements. The aforementioned surfaces through architecting structures of metals and dielectrics all involve challenging nanofabrication instruments [15] , [32] , [33] , [36] .…”
Section: Introductionmentioning
confidence: 99%